(untitled) (مجلة البحوث الأكاديمية, 2026)
The rapid expansion of E-learning in higher education has transformed the way teaching and learning processes are delivered through digital platforms. This study examines the relationships among critical success factors that influence the effectiveness of E-learning systems. The Decision-Making Trial and Evaluation Laboratory (DEMATEL) method was employed to identify and analyze the causal relationships among the main dimensions of E-learning. Five key dimensions were considered: students, instructors, design and content, system and technological infrastructure, and institutional management. Expert evaluations were used to investigate the direct, indirect, and interdependent relationships among these dimensions. The results revealed several important associations among the E-learning success factors. The design and content dimension was identified as the most influential factor affecting the E-learning environment, followed by the system and technological dimension and institutional management. In contrast, the instructors’ and students’ dimensions were found to be primarily influenced by other factors within the system. The cause–effect relationships among the dimensions were identified, and directions for improving E-learning implementation were discussed. The findings provide useful insights for higher education institutions to enhance the effectiveness of E-learning systems by prioritizing improvements in instructional design and technological infrastructure.